Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.